Tryptophan metabolites in depression: Modulation by gut microbiota - Lukić, Iva; Ivković, Sanja; Mitić, Miloš; Adžić, Miroslav (Frontiers in Behavioral Neuroscience, 2022)
Clinical depression is a multifactorial disorder and one of the leading causes of disability worldwide. The alterations in tryptophan metabolism such as changes in the levels of serotonin, kynurenine, and kynurenine acid have been implicated in the etiology of depression for more than 50 years. In recent years, accumulated evidence has revealed that gut microbial communities, besides being essential players in various aspects of host physiology and brain functioning are also implicated in the etiology of depression, particularly through modulation of tryptophan metabolism. Therefore, the aim of this review is to summarize the evidence of the role of gut bacteria in disturbed tryptophan metabolism in depression. We summed up the effects of microbiota on serotonin, kynurenine, and indole pathway of tryptophan conversion relevant for understanding the pathogenesis of depressive behavior. Moreover, we reviewed data regarding the therapeutic effects of probiotics, particularly through the regulation of tryptophan metabolites. Taken together, these findings can open new possibilities for further improvement of treatments for depression based on the microbiota-mediated modulation of the tryptophan pathway.